The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23179619
|View full text |Cite
|
Sign up to set email alerts
|

Magnetofluoro-Immunosensing Platform Based on Binary Nanoparticle-Decorated Graphene for Detection of Cancer Cell-Derived Exosomes

Abstract: Multi-functionalized carbon nanomaterials have attracted interest owing to their excellent synergic properties, such as plasmon resonance energy transfer and surface-enhanced Raman scattering. Particularly, nanoparticle (NP)-decorated graphene (GRP) has been applied in various fields. In this study, silver NP (AgNP)- and magnetic iron oxide NP (IONP)-decorated GRP were prepared and utilized as biosensing platforms. In this case, AgNPs and GRP exhibit plasmonic properties, whereas IONPs exhibit magnetic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In order to further enhance the detection of exosomes with high sensitivity and selectivity, Lee et al have developed a strategy using silver nanoparticles (AgNP) and magnetic iron oxide NP (IONP) decorated on nanoparticle-decorated graphene (GRP) based biosensing platforms for detecting prostate-cancercell-derived exosome (PC-exosome) (Figure 7B). 84 The hybrid nanomaterial consisting of AgNPs, IONP and GRP enabled the system to function as a magneto-plasmonic substrate for magnetofluoro-immunosensing (MFI) system. In this approach, the anti-prostate-specific antigen was immobilized on the Ag/IO-GRP and the PC-exosomes are separated from the sample using an external magnetic force.…”
Section: Dovepressmentioning
confidence: 99%
“…In order to further enhance the detection of exosomes with high sensitivity and selectivity, Lee et al have developed a strategy using silver nanoparticles (AgNP) and magnetic iron oxide NP (IONP) decorated on nanoparticle-decorated graphene (GRP) based biosensing platforms for detecting prostate-cancercell-derived exosome (PC-exosome) (Figure 7B). 84 The hybrid nanomaterial consisting of AgNPs, IONP and GRP enabled the system to function as a magneto-plasmonic substrate for magnetofluoro-immunosensing (MFI) system. In this approach, the anti-prostate-specific antigen was immobilized on the Ag/IO-GRP and the PC-exosomes are separated from the sample using an external magnetic force.…”
Section: Dovepressmentioning
confidence: 99%
“…The study showed that PSMA was over-expressed in patients with prostate cancer, indicating the exosomes in serum as a useful biomarker for the diagnosis [ 193 ]. In another study, an anti-prostate-specific antigen (tetraspanin) was immobilized onto Ag/Fe 3 O 4 /graphene surface to isolate prostate cancer-specific exosomes [ 194 ]. The antibody was conjugated to a dye, and depending on the exosomal concentration, the fluorescence intensity varied.…”
Section: Applications Of Exosomesmentioning
confidence: 99%
“…Inhibition of the process of DNA replacement by the captured p53 protein on the DNA consensus domain provided a decrease in fluorescent emission. Another promising approach for cancer detection war presented by Lee et al [ 77 ], who developed cancer-cell-derived exosomes biosensor via the magnetofluoro-immunosensing (MFI) system using hybrid Ag/iron oxide NP-decorated graphene (Ag/IO-GRP) without purification and concentration processes. The authors successfully detected a prostate-cancer-cell-derived exosome from non-purified exosomes in a culture media sample in a concentration range from 10 2 NPs·mL −1 to 10 6 NPs·mL −1 .…”
Section: Synthetic Magnetic Nanoparticlesmentioning
confidence: 99%